A NEW GENUS OF ICHTHYOSAUR FROM THE LOWER CRETACEOUS OF WESTERN CANADA - Maxwell E.E.; Caldwell M.W. (My University, 2006)
A new fauna of Lower Cretaceous (Albian) ichthyosaurs, which includes at least one new genus and species, was recovered from deposits of the Loon River Formation at Hay River, Northwest Territories, Canada. All Cretaceous ichthyosaurs have been referred to a single genus, Platypterygius. The Loon River Formation material, however, does not satisfy the diagnosis for Platypterygius, and it is distinctive enough to warrant the erection of a new genus and species of ichthyosaur. Maiaspondylus lindoei gen. et sp. nov. is distinguished from other ichthyosaurs by an extensive overlapping contact of the jugal and the maxilla; marginal teeth with smooth crowns, fluted cementum, lingual curvature and implantation in a dental groove; and humerus with isomorphic proximal and distal ends, featuring three distal articular facets in which the medial articular facet is smaller than the lateral facets. The holotype and referred material is described here, and the relationship of Maiaspondylus to other ophthalmosaurs is discussed. © 2006 The Palaeontological Association.
Keywords: CRETACEOUS; ICHTHYOSAURIA; LOON RIVER FORMATION; MAIASPONDYLUS; OPHTHALMOSAURIA; WESTERNINTERIOR SEAWAY; Mesozoic::Cretaceous::Lower::Albian; Мезозой::Меловая::Нижний::Альбский